Collagen‐gelatin‐genipin‐hydroxyapatite composite scaffolds colonized by human primary osteoblasts are suitable for bone tissue engineering applications: In vitro evidences. Issue 5 (20th June 2013) - Vozzi, G.; Corallo, C.; Carta, S.; Fortina, M.; Gattazzo, F.; Galletti, M.; Giordano, N.
Abstract The application of porous hydroxyapatite (HAp)‐collagen as a bone tissue engineering scaffold represents a new trend of mimicking the specific bone extracellular matrix (ECM). The use of HAp in reconstructive surgery has shown that it is slowly invaded by host tissue. Therefore, implant compatibility may be augmented by seeding cells before implantation. Human primary osteoblasts were seeded onto innovative collagen‐gelatin‐genipin (GP)‐HAp scaffolds containing respectively 10%, 20%, and 30% HAp. Cellular adhesion, proliferation, alkaline phosphatase (ALP) activity, osteopontin (OPN), and osteocalcin (OC) expressions were evaluated after 3, 7, 15, and 21 days. The three types of scaffolds showed increased cellular proliferation over time in culture (maximum at 21 days) but the highest was recorded in 10% HAp scaffolds. ALP activity was the highest in 10% HAp scaffolds in all the times of evaluation. OC and OPN resulted in higher concentration in 10% HAp scaffolds compared to 20% and 30% HAp (maximum at 21 days). Finally, scanning electron microscopy analysis showed progressive scaffolds adhesion and colonization from the surface to the inside from day 3 to day 21. In vitro attachment, proliferation, and colonization of human primary osteoblasts on collagen‐GP‐HAp scaffolds with different percentages of HAp (10%, 20%, and 30%) all increased over time in culture, but comparing different percentages of HAp, they seem to increase with decreasing of HAp component. Therefore, the mechanical properties (such as the stiffness due to the HAp%) coupled with a good biomimetic component (collagen) are the parameters to set up in composite scaffolds design for bone tissue engineering. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1415–1421, 2014.